(untitled) (Journal of Education and Development, 2018)
Public health seeks to protect and improve the health of communities through the promotion of healthy lifestyles, research for disease and injury prevention, and detection and control of infectious diseases. It is a population-focused science that works primarily with prevention strategies, policies implementation, service administration, and research. While this field seemingly contrasts with the field of clinical medicine—in which patients are treated on an individual level after becoming sick or injured—public health concepts regarding prevention are critical knowledge areas for any health professional. In recent years, public health courses have been incorporated into degree requirements for a variety of health-related professions; however, several studies have indicated that health professions students have negative attitudes toward these courses for a variety of reasons. Given the importance of public health as a crucial component of health profession education, it is important to understand how students’ perceptions of public health education are shaped to ensure effective integration.